2022
DOI: 10.1177/10998004221078079
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Energy Restriction for Weight Loss: A Systematic Review of Cardiometabolic, Inflammatory and Appetite Outcomes

Abstract: Current guidelines for obesity treatment recommend reducing daily caloric intake for weight loss. However, long-term weight loss continues to be an issue in obesity management. Alternative weight loss strategies have increased in popularity, such as intermittent energy restriction (IER), a type of eating pattern with periods of fasting alternating with unrestricted eating. The effects of IER on weight loss, cardiovascular risk factors, inflammation, and appetite are not clear. The purpose of this systematic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(29 citation statements)
references
References 62 publications
0
28
0
1
Order By: Relevance
“…When compared with an ad libitum diet, 10 reviews found fasting glucose to be significantly reduced during IF, 10,16,21,22,24,29,30,[40][41][42] whereas nine reviews found that there was no significant difference compared to an ad libitum diet. 5,6,13,17,20,25,26,28,37 All seven reviews that reported HbA1c levels found no significant difference between IF and control groups. 5,14,21,25,29,30,37 Four of these reviews did not include any participants with T2D and therefore most participants did not have any glucose abnormalities at baseline.…”
Section: If Versus Ad Libitummentioning
confidence: 97%
See 4 more Smart Citations
“…When compared with an ad libitum diet, 10 reviews found fasting glucose to be significantly reduced during IF, 10,16,21,22,24,29,30,[40][41][42] whereas nine reviews found that there was no significant difference compared to an ad libitum diet. 5,6,13,17,20,25,26,28,37 All seven reviews that reported HbA1c levels found no significant difference between IF and control groups. 5,14,21,25,29,30,37 Four of these reviews did not include any participants with T2D and therefore most participants did not have any glucose abnormalities at baseline.…”
Section: If Versus Ad Libitummentioning
confidence: 97%
“…The remaining review that included participants with T2D did not specify a count. 26 Ten reviews found no difference in fasting glucose between IF and CER. One review found mixed results attributed to the heterogeneity of studies.…”
Section: If Versus Cermentioning
confidence: 99%
See 3 more Smart Citations